Intended and experienced literacy practices in a Swedish undergraduate nursing education - Maria Christidis; Nikolaos Christidis; Viveca Lindberg; Kristina Gottberg; Carina Georg (PLoS ONE, 2025)
Introduction Academic literacy in higher education has been widely studied, but less attention has been given to literacy practices within professional programmes such as nursing education. This study aimed to analyze one Swedish undergraduate nursing programme regarding the presence of academic and professional literacy, and secondarily to explore students’ note-taking as a component of literacy practices. Methods The study employed a descriptive and exploratory design, analyzing curriculum documents and surveying nursing students. An analysis of the intended curriculum (course syllabi) of a three-year undergraduate nursing programme at Karolinska Institutet was conducted to identify explicit and implicit literacy components. A digital questionnaire focusing on note-taking practices was distributed to second-semester students (n = 67; response rate 40%). Closed questions were analyzed using descriptive statistics, while open-ended responses underwent qualitative content analysis. Results The curriculum analysis demonstrated that academic literacy was primarily addressed through scientific writing, group projects, and thesis work, particularly in the first two and final two semesters. Professional literacy was integrated across all semesters and included communication with patients, families, and interprofessional teams, documentation, and interpretation of professional texts. Surveyed students reported frequent note-taking, primarily during lectures and prior to examinations, using both pen and paper and digital devices, with a preference for pen and paper. Qualitative data indicated that students use note-taking mainly to support memorization, understanding, and exam preparation, with limited focus on professional literacy needs. Conclusion The nursing curriculum integrates both academic and professional literacy practices, although with different emphases across the study period. Students’ current note-taking practices are predominantly academically oriented. These findings highlight the need for more explicit integration and scaffolding of both academic and professional literacy throughout nursing education to better prepare students for their future professional roles, i.e., for clinical communication, documentation, and interprofessional collaboration essential to safe and effective patient care.